The role of mGluR5 on the therapeutic effects of ketamine in Wistar rats. - Gokalp, Dilan; Unal, Gunes (Psychopharmacology, 2024)
Rationale: Ketamine produces dissociative, psychomimetic, anxiolytic, antidepressant, and anesthetic effects in a dose dependent manner. It has a complex mechanism of action that involve alterations in other glutamate receptors. The metabotropic glutamate receptor 5 (mGluR5) has been investigated in relation to the psychotic and anesthetic properties of ketamine, while its role in mediating the therapeutic effects of ketamine remains unknown. Objectives: We investigated the role of mGluR5 on the antidepressant, anxiolytic and fear memory-related effects of ketamine in adult male Wistar rats. Methods: Two sets of experiments were conducted. We first utilized the positive allosteric modulator CDPPB to investigate how acute mGluR5 activation regulates the therapeutic effects of ketamine (10 mg/kg). We then tested the synergistic antidepressant effect of mGluR5 antagonism and ketamine by combining MTEP with a sub-effective dose of ketamine (1 mg/kg). Behavioral despair, locomotor activity, anxiety-like behavior, and fear memory were respectively assessed in the forced swim test (FST), open field test (OFT), elevated plus maze (EPM), and auditory fear conditioning. Results: Enhancing mGluR5 activity via CDPPB occluded the antidepressant effect of ketamine without changing locomotor activity. Furthermore, concomitant administration of MTEP and ketamine exhibited a robust synergistic antidepressant effect. The MTEP + ketamine treatment, however, blocked the anxiolytic effect observed by sole administration of MTEP or the low dose ketamine. Conclusions: These findings suggest that suppressed mGluR5 activity is required for the antidepressant effects of ketamine. Consequently, the antagonism of mGluR5 enhances the antidepressant effectiveness of low dose ketamine, but eliminates its anxiolytic effects.